IMPROVED GIN SAW CYLINDER - Abduvaxidov, Mutaxxirxon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article discusses the design of the saw cylinder of the genie DP-130 family. Ways to improve performance have been studied. A shaft with a hexagonal cross-section was considered as an energy- and resource-saving design.